Dynamic Trapping as a Selective Route to Renewable Phthalide from Biomass‐Derived Furfuryl Alcohol - Lancefield, Christopher S.; Fölker, Bart; Cioc, Razvan C.; Stanciakova, Katarina; Bulo, Rosa E.; Lutz, Martin; Crockatt, Marc; Bruijnincx, Pieter C. A. (Angewandte Chemie International Edition, 2020)
A novel route for the production of the versatile chemical building block phthalide from biorenewable furfuryl alcohol and acrylate esters is presented. Two challenges that limit sustainable aromatics production via Diels–Alder (DA) aromatisation—an unfavourable equilibrium position and undesired regioselectivity when using asymmetric addends—were addressed using a dynamic kinetic trapping strategy. Activated acrylates were used to speed up the forward and reverse DA reactions, allowing for one of the four DA adducts to undergo a selective intramolecular lactonisation reaction in the presence of a weak base. The adduct is removed from the equilibrium pool, pulling the system completely to the product with a fixed, desired regiochemistry. A single 1,2‐regioisomeric lactone product was formed in up to 86 % yield and the acrylate activating agent liberated for reuse. The lactone was aromatised to give phthalide in almost quantitative yield in the presence of Ac2O and a catalytic amount of strong acid, or in 79 % using only catalytic acid. An intramolecular trapping strategy allows inherent problems in the Diels–Alder reaction of biomass‐derived furfuryl alcohol, such as regioselectivity and unfavourable equilibrium yields, to be overcome on the way to biomass‐derived aromatics. This strategy provides a high yielding, redox and atom economical approach to produce the versatile phthalide synthon.